PCSK9 inhibition with evolocumab (AMG 145) in heterozygous familial hypercholesterolaemia (RUTHERFORD-2): a randomised, double-blind, placebo-controlled trial. Issue 9965 (24th January 2015) - Raal, Frederick J; Stein, Evan A; Dufour, Robert; Turner, Traci; Civeira, Fernando; Burgess, Lesley; Langslet, Gisle; Scott, Russell; Olsson, Anders G; Sullivan, David; Hovingh, G Kees; Cariou, Bertrand; et al.
Summary: Background: Heterozygous familial hypercholesterolaemia is characterised by low cellular uptake of LDL cholesterol, increased plasma LDL cholesterol concentrations, and premature cardiovascular disease. Despite intensive statin therapy, with or without ezetimibe, many patients are unable to achieve recommended target levels of LDL cholesterol. We investigated the effect of PCSK9 inhibition with evolocumab (AMG 145) on LDL cholesterol in patients with this disorder. Methods: This multicentre, randomised, double-blind, placebo-controlled trial was undertaken at 39 sites (most of which were specialised lipid clinics, mainly attached to academic institutions) in Australia, Asia, Europe, New Zealand, North America, and South Africa between Feb 7 and Dec 19, 2013. 331 eligible patients (18–80 years of age), who met clinical criteria for heterozygous familial hypercholesterolaemia and were on stable lipid-lowering therapy for at least 4 weeks, with a fasting LDL cholesterol concentration of 2·6 mmol/L or higher, were randomly allocated in a 2:2:1:1 ratio to receive subcutaneous evolocumab 140 mg every 2 weeks, evolocumab 420 mg monthly, or subcutaneous placebo every 2 weeks or monthly for 12 weeks. Randomisation was computer generated by the study sponsor, implemented by a computerised voice interactive system, and stratified by LDL cholesterol concentration at screening (higher or lower than 4·1 mmol/L) and by baseline ezetimibe use (yes/no). Patients, study personnel, investigators, and Amgen study staff were masked to treatment assignments within dosing frequency groups. The coprimary endpoints were percentage change from baseline in LDL cholesterol at week 12 and at the mean of weeks 10 and 12, analysed by intention-to-treat. This trial is registered withClinicalTrials.gov, numberNCT01763918 . Findings: Of 415 screened patients, 331 were eligible and were randomly assigned to the four treatment groups: evolocumab 140 mg every 2 weeks (n=111), evolocumab 420 mg monthly (n=110), placebo every 2 weeks (n=55), or placebo monthly (n=55). 329 patients received at least one dose of study drug. Compared with placebo, evolocumab at both dosing schedules led to a significant reduction in mean LDL cholesterol at week 12 (every-2-weeks dose: 59·2% reduction [95% CI 53·4–65·1], monthly dose: 61·3% reduction [53·6–69·0]; both p<0·0001) and at the mean of weeks 10 and 12 (60·2% reduction [95% CI 54·5–65·8] and 65·6% reduction [59·8–71·3]; both p<0·0001). Evolocumab was well tolerated, with rates of adverse events similar to placebo. The most common adverse events occurring more frequently in the evolocumab-treated patients than in the placebo groups were nasopharyngitis (in 19 patients [9%] vs five [5%] in the placebo group) and muscle-related adverse events (ten patients [5%] vs 1 [1%]). Interpretation: In patients with heterozygous familial hypercholesterolaemia, evolocumab administered either 140 mg every 2 weeks or 420 mg monthly was well tolerated and yielded similar and rapid 60% reductions in LDL cholesterol compared with placebo. Funding: Amgen Inc.